The Effects Of Indentation Loading Force And Number Of Indentations On The Micro Hardness Variation For Inconel 718 - W. Mohamad, W Noor Fatihah; Kasim, Mohd Shahir; Mohd Zakaria, Muhammad Akmal; Mohd Shahrim, Mohammad Shah All Hafiz; Mohamed, Saiful Bahri (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The accuracy of the hardness test depends on the effects of variations of the loading force and the number of indentations. The purpose of this study was to compare the micro hardness data of these factors. Aged Inconel 718 with a hardness of 450 HV was used as the specimen in this test. The investigation was carried out by observing the amount of dispersion in a set of hardness data at different loads and number of indentations. The applied loading force ranged from 0.05 to 0.3 Kgf, while the number of indentations was set from 10 to 30. From the result, it was found that increasing the applied load brought the hardness value close to the standard hardness of the material. However, an increase in the number of indentations failed to produce an accurate value.